SOLVE AND SHOW SOLUTION
[tex](x+8) (3x²+23x-8)[/tex]



Sagot :

Answer:

(x + 8)2 • (3x - 1)

Step-by-step explanation:

The first term is, 3x2 its coefficient is 3 .

The middle term is, +23x its coefficient is 23 .

The last term, "the constant", is -8

Step-1 : Multiply the coefficient of the first term by the constant 3 • -8 = -24

Step-2 : Find two factors of -24 whose sum equals the coefficient of the middle term, which is 23 .

-24 + 1 = -23

-12 + 2 = -10

-8 + 3 = -5

-6 + 4 = -2

-4 + 6 = 2

-3 + 8 = 5

-2 + 12 = 10

-1 + 24 = 23 That's it

Answer:

Tama po yung sagot nya ⬆️⬆️⬆️